Cities insane - Odufuwa, Bashir Olufemi; Ogunseye, Nathaniel Oluwaseun; Salisu, Umar Obafemi; Fasina, Simeon Oluwagbenga (Penerbit Universiti Kebangsaan Malaysia, 2018)
Globally, cities are known to be the engines of development. Meanwhile, the failure of most Nigerian cities to satisfy the needs of city dwellers has increasingly become an issue of discourse in recent times. These inadequacies have been blamed on the unguided urbanization rate in most developing countries. Population increases and poor governance in most Sub-Saharan African cities are responsible for the increasing demands for social and economic services which invariably affect the level of satisfaction of city residents. This situation has partly necessitated the global urban campaign for liveable cities. This study assessed the satisfaction of residents in five Nigerian cities using a questionnaire survey. Stratified and random sampling methods were used to select 765 respondents so as to elicit information on city-living. The variables that determined the satisfaction of city residents were identified. Most of the respondents (82%) were not satisfied with the cities due to the inadequate electricity/power supply, water, sanitation, transport, security, and health services in the cities. A chi-square analysis showed that the calculated values for the satisfaction with regard to selected variables of electricity supply [7.314]; transport [9.737]; recreation [12.024]; health [9.737]; telecommunication [21.291]; waste management [18.604] and water supply [23.988] in cities were less than the table value (31.41) at an alpha level of 0.05. This implied that there was no significant difference in the level of satisfaction. A factor analysis revealed the major determinants – reliable power supply, improved transport and water supply, employment opportunities, good medical services, enhanced food security – that can improve the level of satisfaction with cities. Based on the findings, the implications of poorly serviced and managed cities on residents and national development were discussed.